PENGARUH LAYANAN INFORMASI TERHADAP MOTIVASI BELAJAR SISWA KELAS VIII SMP DI KOTA JAMBI - Yusra, Affan (Program Studi Bimbingan dan Konseling FKIP UNJA, 2022)
Learning motivation is a force that can be a driving force for students to utilize their inner and outer potential to realize learning goals. One way that can be used is the provision of information services. The aims of this study were: to reveal the learning motivation of class VIII junior high school students in Jambi City before being provided with information services, to reveal the learning motivation of VIII junior high school students in Jambi City after being provided with information services, and to reveal the effect of information services on the learning motivation of VIII junior high school students in Jambi City. . This type of research is an experiment with a pretest and post-test design. The data that has been obtained is then collected through pretest and post-test, then analyzed using t-test with the help of SPSS version 20. The findings of this study are: the pre-test score of the experimental class, an overall average of about 50.82% of students have learning motivation which is in the low category and while the post-test score, about 71.58% on average, all students have learning motivation in the very high category there is a difference of 20.76%, the control class pre-test score of 51.01% of students is in the low category while the post-test score, about 65.85% of students who have learning motivation are in the low category. very good difference of about 14.84%, and it is concluded based on the data it can be interpreted that learning motivation increases after being given treatment in the form of information services.